The effect of genetic group and some non-genetic factors in live weight at slaughtering and number of carcass traits in Local and Cyprian male goats and their crosses*. - سالم, عبدالله حميد; سعيد, سعد ابراهيم; سعيد, سعد ابراهيم; طه, صادق علي (Journal of Kerbala for Agricultural Sciences, 2015)
This study was conducted at Ruminants Researches Station / Directorate of Agricultural Researches /Ministry of Agriculture during January 20,2014 until October 1,2014.The aims of research was study the effect of genetic group and some non-genetic factors on the animal live weight at slaughtering and some carcass traits which aged 10 months in male goats.It included 93 goat males consist of 45 Cyprian goat males(C) , 25 Local goat males(L) ,18 Intercrossing /1 goat males (♂1/2 L+1/2 C ×♀1/2 L+1/2 C) and 5 Intercrossing/ 2 goat males (♂L×♀C) . The overall means of live slaughter ,empty body, hot and chilled carcass weights were 23.186,18.952,9.877 and 9.563 kg respectively. The overall mean of dressing percentages based of live and empty body were 39.60% and 52.17% respectively . The prime cuts percentages overall means based to half cold carcass were 27.26 ,10.36 ,32.37 and 7.34% for shoulder , racks ,leg and lion respectively. while the overall means of coarse cuts percentages were 7.46 ,6.19 ,1.99 and 6.98% for for-shank ,breast ,flank and neck respectively.The overall means of rib eye area, fat thickness , pelvic &kidney fat, heart fat and omental fat were7.76 cm2, 0.54 mm, 33.58, 10.53 and 40.36 gm respectively. None of the studied traits were affected significantly by genetic group (except breast cut and heart fat ), despite of superiority of Intercrossing's /2 and 1 in most of studied traits means. Key words : genetic group , carcass traits , goat. *The research was winkling from Ph.D Thesis of first researcher .